Full-battery effect during on-board solar charging of conventional vehicles. (July 2021) - Lodi, Chiara; Gil-Sayas, Susana; Currò, Davide; Serra, Simone; Drossinos, Yannis
Graphical abstract: CO2 savings in g/km arising from a battery-charging PV roof in petrol vehicles as a function of the normalized vehicle storage capacity L 1 = C wh / (mPp cosθ η PVS   Δ t ) and the normalized vehicle power consumption L 2 = Prw / (mPp cosθ η PVS ) with mPp the photovoltaic array total peak power, θ its inclination angle, η PVS the efficiency of the PV system, and Δ t the simulation time. mPp = 200 W, η PVS = 0.7544, θ = 0, Δt = 1 h/60. Two daily driving periods. Left: 3-D representation. Right: Equally-spaced contours. Highlights: The full-battery effect is the loss of storable solar energy for battery saturation. A significant fraction of solar energy may be lost due to the full-battery effect. Electric power consumption is the main parameter influencing the full-battery effect. The full-battery effect can be minimized by optimizing storage capacity and PV power. CO2 savings from PV arrays increase when three daily driving periods are considered. Abstract: On-board photovoltaic arrays may reduce fuel consumption and contribute to decarbonization of road transport by feeding the electric storage capacity of a vehicle. Since the CO2 savings arising from this technology cannot be quantified by standard test-cycle CO2 measurements, additional procedures are considered to assess its performance under real-world driving. The full-battery effect, i.e., the loss of potentially storable solar energy due to battery saturation, influences significantly these savings. The objective of this study is to present a novel methodology to evaluate the impact of the full-battery effect during on-board solar charging of conventional vehicles and thereby to estimate the associated CO2 savings. The methodology is based on solar irradiance and driver mobility data. Results show that the full-battery effect can be uniquely determined by the normalized real-world solar irradiance and two dimensionless combinations of vehicle electric power consumption, solar-energy storage capacity, system efficiency, PV array peak power and inclination.